1998
DOI: 10.1177/000992289803700404
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health, Lung Function, and Airway Responsiveness in School-Age Survivors of Very-Low-Birt-Weight

Abstract: The purpose of this study was to determine the respiratory symptoms, pulmonary function, and airway reactivity in school-age survivors of very-low-birth-weight and to describe the influence of birth weight and perinatal illness on their pulmonary function. Thirty (of 39) 10- to 11-year-old survivors of very-low-birth-weight (VLBW) recruited at birth into a prospective longitudinal study of development; 30 (of 32) normal-birth-weight peers recruited from the same school or census tract as the VLBW group at age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
(3 reference statements)
0
7
0
6
Order By: Relevance
“…Infants in the NICU often require cardiac and pulmonary monitoring with oxygen therapy or mechanical ventilation at some point during their admission (Apisarnthanarak, Holzmann-Pazgal, Hamvas, Olsen, & Fraser, 2003;Patel, Beeby, & Henderson-Smart, 2003). The prevalence of underlying chronic pulmonary disease including bronchopulmonary dysplasia, apnea, and reactive airway disease in NICU infants reaches 20% (Manktelow, Draper, Annamalai, & Field, 2001;Schraeder, Czajka, Kalman, & McGeady, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Infants in the NICU often require cardiac and pulmonary monitoring with oxygen therapy or mechanical ventilation at some point during their admission (Apisarnthanarak, Holzmann-Pazgal, Hamvas, Olsen, & Fraser, 2003;Patel, Beeby, & Henderson-Smart, 2003). The prevalence of underlying chronic pulmonary disease including bronchopulmonary dysplasia, apnea, and reactive airway disease in NICU infants reaches 20% (Manktelow, Draper, Annamalai, & Field, 2001;Schraeder, Czajka, Kalman, & McGeady, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45] Historically, the greater incidence of respiratory diseases observed in children born prematurely has been attributed to two factors: pulmonary immaturity and the intensity of the ventilatory support used during the neonatal period. [29][30][31][33][34][35][36][46][47][48] McLeod et al 29 found an association between reduced flows and forced vital capacity (FVC) in premature infants who had needed MV for periods longer than 28 days and/or extended oxygen use at concentrations over 40% during neonatal hospital care.…”
Section: Functional Assessment During the First Years Of Lifementioning
confidence: 99%
“…Although some studies have demonstrated improvements in respiratory symptoms and even in pulmonary function as childhood and adolescence progress, 34,48,61,[64][65][66] there is increasing evidence that many abnormalities may persist until late childhood or even adulthood. 31,33,46,50,55,65,67,68 Doyle,66 measuring the pulmonary function of premature infants born at less than 1,000 g at 14 years of age and comparing them with fullterm controls, reported that, while the incidence of symptoms and the prevalence of asthma and re-hospitalizations were similar for the two groups even for those who had BPD, expiratory flow was reduced for premature infants (32% versus 8% for the controls), with 22% exhibiting clinical repercussions.…”
Section: Premature Children Without Bpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Many babies who begin life needing NICU care develop chronic conditions affecting their respiratory health (Manktelow, Draper, Annamalai, & Field, 2001;Schrader, Czajka, Kalman & McGeady, 1998). In the United States, the estimated smokingattributable neonatal expenditure was over $148.5 million in 2003 (Centers for Disease Control and Prevention [CDC], 2011).…”
mentioning
confidence: 99%